Perfil epidemiológico e clínico de crianças com nevo melanocítico congênito gigante em um serviço de dermatologia - Bruna Cavaleiro de Macêdo Souza; Ana Carolina Batista Pamplona de Freitas; Lorena de Britto Pereira da Cruz; Carla Andrea Avelar Pires; Jaqueline Azevedo Leão; Thais Suellen Ramos Allen; Maria Amelia Lopes Santos (Sociedade Brasileira de Pediatria, 2023)
OBJECTIVE: to describe five children with Congenital Giant Melanocytic Nevus (NMCG) at the Dermatology Service at the State University of Pará in Belém - PA, Brazil. CASE DESCRIPTION: patients aged 1 to 11 years, four of whom were female, all of them brown, in good nutritional status, prenatal without complications, and denied consanguinity. The five cases presented lesions on the trunk, with different distribution patterns: swimming trunks (1), body (1), back (1), and bolero (2), most with more than fifty satellite lesions containing hypertrichosis and pruritus. In the histopathological analysis, all of them were compatible with a nevus, one of the cases was associated with a neurofibroma, two with neurocutaneous melanosis and one with melanoma in the brain, evolving to death. COMMENTS: Congenital Giant Melanocytic Nevus is a rare condition, defined by the presence of a melanocytic lesion, measuring at least 20 cm, present since birth. It has its clinical relevance due to the association with serious complications such as melanoma and / or neurocutaneous melanosis. The registration of this series aims to contribute to greater knowledge about the disease, which has physical, psycho-emotional, social, and risk of malignancy implications.